Behavioral intervention in adolescents improves bone mass, yet lactose maldigestion is a barrier - Lee, Y.; Savaiano, D.; McCabe, G.; Pottenger, F.; Welshimer, K.; Weaver, C.; McCabe, L.; Novotny, R.; Read, M.; Going, S.; Mason, A.; Van Loan, M.; et al. (MDPI Publishing, 2018)
Calcium intake during adolescence is important for attainment of peak bone mass. Lactose maldigestion is an autosomal recessive trait, leading to lower calcium intake. The Adequate Calcium Today study aimed to determine if a school-based targeted behavioral intervention over one year could improve calcium intake and bone mass in early adolescent girls. The school-randomized intervention was conducted at middle schools in six states over one school year. A total of 473 girls aged 10–13 years were recruited for outcome assessments. Bone mineral content (BMC) was determined by dual energy X-ray absorptiometry. Dietary calcium intake was assessed with a semi-quantitative food frequency questionnaire. Baseline calcium intake and BMC were not significantly different between groups. After the intervention period, there were no differences in changes in calcium intake and BMC at any site between groups. An unanticipated outcome was a greater increase in spinal BMC among lactose digesters than lactose maldigesters in the intervention schools only (12 months) (6.9 ± 0.3 g vs. 6.0 ± 0.4 g, p = 0.03) and considering the entire study period (18 months) (9.9 ± 0.4 vs. 8.7 ± 0.5 g, p < 0.01). Overall, no significant differences between the intervention and control schools were observed. However, lactose digesters who received the intervention program increased bone mass to a greater extent than lactose maldigesters.